Victim Impact Statement as a Model of Victim-Centered Justice in Child Sexual Abuse Cases - Ramadianto, Anang Riyan; Istiqomah, Milda; Aprilianda, Nurini (Jurnal Hukum IUS QUIA IUSTUM, 2025)
Child sexual abuse remains a pressing concern in Indonesia, with victims often experiencing deep and lasting trauma. Yet, the country’s criminal justice system largely focuses on punishing offenders, offering far less attention to safeguarding and supporting the rights and recovery of those who have suffered. This article aims to explore the role of the Victim Impact Statement (VIS) as a mechanism to promote victim-centered justice. This study adopts a normative legal research approach, drawing on statutory analysis, comparative review, and case study methods. Its primary legal sources include court rulings on child sexual abuse and key regulations, notably Supreme Court Regulation (PERMA) No. 1 of 2022 on Restitution and Compensation. Data are analyzed qualitatively to evaluate the implementation of restitution and the recognition of victim perspectives in legal proceedings. The findings indicate that restitution is essential in incorporating the victim’s voice into judicial decision-making. The study proposes a Victim Impact Statement (VIS) model designed to help both victims and judges convey and evaluate the effects of crime more effectively. It concludes with recommendations to better integrate VIS into Indonesia’s criminal justice system, moving toward an approach that is more victim-centered and aligned with the principles of restorative justice.